EFEKTIFITAS TEKNIK BERANGSUR UNTUK MENINGKATKAN KEMAMPUAN MENULIS HURUF SAMBUNG PADA ANAK BERKESULITAN BELAJAR MENULIS - Dwi Yulinda, Ganda Sumekar, Kasiyati (Universitas Negeri Padang, 2013)
This research is motivated by problems that researchers in the field discovered that a child's learning disabilities in grade II / A who have difficulty writing. This research uses experimental approach with methods Single Subject Research (SSR) with design A1-B-A2. On condition invertensi child's ability increases, this activity is done seven times observation, which was originally the child reaches 40% and finally the child is able to write a word using the letters connect properly and clearly reaches 90%. And the Baseline condition 2, the activities carried out under these conditions five times observation after invertensi activity is stopped, it turns out the child's ability to retain the ability to write words using the letters connect properly and clearly. Thus the previously proposed hypothesis can be accepted, it means that the technique can gradually boost Traffic continued to write letters to children learning disabilities class x II / A in SDN 02 Padang Cupak Tangah. The researchers suggest to teachers to use the fade techniques to improve writing letters continued future learning disabilities in children.